Pulmonary Function Test Among University Students-A Cross Sectional Survey - Hina Saeed, Rahila Yousuf, Sobia Hasan, M. Muddasir Ansari, Tehreem Anis, Sanowber Ajaz (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To identify the lung functioning parameters i.e. FVC, FEV1, FEV1/FVC%, MVV of healthy individuals with normal pulmonary function. Study Design: It was a cross-sectional study. Study Setting: Study was conducted at Institute of Physical and Medical Rehabilitation (IPM&R), Dow University of Health Sciences (DUHS), Karachi, Pakistan from August 2022 to January 2023. Methods: Total 60 students giving the male to female ratio of 1:1 with age ranging of 15-30 years were enrolled and studied for respiratory functions by spirometry. Subjects were divided in two groups depending on their gender. The Measured parameters comprised: Vital capacity (VC), forced vital capacity (FVC), forced expiratory volume first second (FEV1), FEV1/FVC%, and maximum voluntary ventilation (MVV). Result: Our results show that all indices, including FVC, FEV1, FVC/FEV1%, and MVV, were statistically significantly (p0.01) greater in males compared to females. Women have a much lower FEV1/FVC ratio than men do (p< 0.05). Out of a total of 60 students, 57.3% (n=34) were classified as having normal spirometry; 15.3% (n=9) were classified as having mild restrictions; 11.7% (n=7) were classified as having moderate restrictions; 1.7% (n=1) were classified as having moderate severe restrictions; 10% (n=6) were classified as having mild obstruction; and 5.3% (n=3) were classified as having moderate obstruction. Practical Implication: Little data exist on whether and how PFT parameters change depending on a person’s gender. As a result, we set out to learn more about the differences between the sexes in PFT variables and the connection between BMI and the tests. Conclusion: Our study revealed that males had greater values of FVC, FEV1, FVC/FEV1, and MVV when compared to females, which was statistically significant (p<0.01). Females have a significantly (p0.05) lower FEV1/FVC ratio than males. Our findings demonstrate that healthy male and female subjects breathe in different ways, which may be related to gender’s effect on lung function. Keywords: Gender, Spirometer, FVC, FEV1, FEV1 /FVC%, MVV, Medical Rehabilitation, Pulmonary Function